DNAJC30 disease-causing gene variants in a large Central European cohort of patients with suspected Leber's hereditary optic neuropathy and optic atrophy. Issue 10 (28th January 2022) - Kieninger, Sinja; Xiao, Ting; Weisschuh, Nicole; Kohl, Susanne; Rüther, Klaus; Kroisel, Peter Michael; Brockmann, Tobias; Knappe, Steffi; Kellner, Ulrich; Lagrèze, Wolf; Mazzola, Pascale; Haack, Tobias B; et al.
Abstract : Background: Leber's hereditary optic neuropathy (LHON) has been considered a prototypical mitochondriopathy and a textbook example for maternal inheritance linked to certain disease-causing variants in the mitochondrial genome. Recently, an autosomal recessive form of LHON (arLHON) has been described, caused by disease-causing variants in the nuclear encoded gene DNAJC30 . Methods and results: In this study, we screened the DNAJC30 gene in a large Central European cohort of patients with a clinical diagnosis of LHON or other autosomal inherited optic atrophies (OA). We identified likely pathogenic variants in 35/1202 patients, corresponding to a detection rate of 2.9%. The previously described missense variant c.152A>G;p.(Tyr51Cys) accounts for 90% of disease-associated alleles in our cohort and we confirmed a strong founder effect. Furthermore, we identified two novel pathogenic variants in DNAJC30 : the nonsense variant c.610G>T;p.(Glu204*) and the in-frame deletion c.230_232del;p.(His77del). Clinical investigation of the patients with arLHON revealed a younger age of onset, a more frequent bilateral onset and an increased clinically relevant recovery compared with LHON associated with disease-causing variants in the mitochondrial DNA. Conclusion: This study expands previous findings on arLHON and emphasises the importance of DNAJC30 in the genetic diagnostics of LHON and OA in European patients.